Phenomics and genomics approaches in improving Tagnanan population towards increasing MATAG production efficiency - Naharudin, Nazatul Shima; Sinniah, Uma Rani; Mohamad Zaki, Nurqistina Atiqah; Kingimi, Mohammed (Faculty of Agriculture, UPM, 2024)
As one of the main coconut hybrid varieties in Malaysia, there is a high demand on MATAG seedlings production. The seedlings are produced by hand pollinating Malayan Dwarf with pollen from Tagnanan, a tall coconut variety. Tagnanan is allogamous in nature, therefore the population possess considerable heterogeneity in yield and performance. Consequently, this condition affects the current hybridization success rate in producing uniform and genuine MATAG. A strategy to improve Tagnanan population by incorporating phenotypic and genomics approaches could expedite the process to increase the efficiency of MATAG seedlings production. A sample of 100 Tagnanan individuals were chosen to acquire phenotypic data regarding growth, yield, and fruit quality. Genomic DNA were extracted from young leaf samples of these individuals to develop genotypic data using polymorphic microsatellite markers. This approach has successfully shown that the current Tagnanan population used as pollen source in MATAG seed production have moderate variation for yield traits, namely meat weight (CV – 26%), water volume (CV – 32%), fruit size (CV – 33%) and husk weight (CV – 53%). The genotypic data was used to estimate population parameters including Shannon’s diversity index (I) of 0.699 and Nei’s index (h) of 0.4708, indicating moderate allelic variation and heterozygosity in the sample population. Selection of high yielding individuals were also made possible with the identification of 11 putative SSR markers associated with yield and fruit quality traits. These findings increase the precision of selecting high performing Tagnanan individuals for the purpose of developing improved and homogenous Tagnanan population in one selection cycle.